Real-World Evidence Comparing Vedolizumab and Ustekinumab in Antitumor Necrosis Factor-Experienced Patients With Crohn's Disease. (26th April 2023) - Kappelman, Michael D.; Adimadhyam, Sruthi; Hou, Laura; Wolfe, Audrey E.; Smith, Samantha; Simon, Andrew L.; Moyneur, Érick; Reynolds, Juliane S.; Toh, Sengwee; Dobes, Angela; Parlett, Lauren E.; Haynes, Kevin; et al.
Abstract : INTRODUCTION: Many patients with Crohn's disease (CD) lose response or become intolerant to antitumor necrosis factor (TNF) therapy and subsequently switch out of class. We compared the effectiveness and safety of ustekinumab to vedolizumab in a large, geographically diverse US population of TNF-experienced patients with CD. METHODS: We conducted a retrospective cohort study using longitudinal claims data from a large US insurer (Anthem, Inc.). We identified patients with CD initiating vedolizumab or ustekinumab with anti-TNF treatment in the prior 6 months. Our primary outcome was treatment persistence for >52 weeks. Secondary outcomes included (i) all-cause hospitalization, (ii) hospitalization for CD with surgery, (iii) hospitalization for CD without surgery, and (iv) hospitalization for infection. Propensity score fine stratification was used to control for demographic and baseline clinical characteristics and prior treatments. RESULTS: Among 885 new users of ustekinumab and 490 new users of vedolizumab, we observed no difference in treatment persistence (adjusted risk ratio 1.09 [95% confidence interval 0.95–1.25]). Ustekinumab was associated with a lower rate of all-cause hospitalization (adjusted hazard ratio 0.73 [0.59–0.91]), nonsurgical CD hospitalization (adjusted hazard ratio 0.58 [0.40–0.83]), and hospitalization for infection (adjusted hazard ratio 0.56 [0.34–0.92]). DISCUSSION: This real-world comparative effectiveness study of anti-TNF-experienced patients with CD initiating vedolizumab or ustekinumab showed similar treatment persistence rates beyond 52 weeks, although secondary outcomes such as all-cause hospitalizations, nonsurgical CD hospitalizations, and hospitalizations for infection favored ustekinumab initiation. We, therefore, advocate for individualized decision making in this medically refractory population, considering patient preference and other factors such as cost and route of administration.